A Comparison of Magnetic Resonance Imaging Muscle Fat Content in the Lumbar Paraspinal Muscles with Patient-Reported Outcome Measures in Patients with Lumbar Degenerative Disk Disease and Focal Disk Prolapse. (June 2016) - Bhadresha, Ashwin; Lawrence, Owen John; McCarthy, Michael J. H.
Study Design: Retrospective study. Objectives: To assess the fatty atrophy of the lumbar paraspinal muscles (LPMs) as determined using magnetic resonance imaging in patients with lumbar degenerative disk disease (DDD) and focal disk herniation and to determine if fatty atrophy is associated with patient-reported outcome measures (PROMS). Methods: One hundred sixty-five patients with lumbar DDD were identified from a PROMS database of >1, 500 patients. These patients were divided into two study groups: DDD alone ( n = 58) and DDD with disk herniation ( n = 107). A grid was randomly applied to the axial scans at the L3–L4, L4–L5, and L5–S1 levels. The muscle-to-fat ratio of the LPMs was recorded and compared with PROMS data. Subcutaneous fat thickness at each level was also measured. Results: This study found no difference in the muscle-to-fat ratio between the DDD and disk herniation groups. There was no association between the muscle-to-fat ratio and PROMS data in either group. There was significantly more subcutaneous fat at all levels in the DDD group as compared with the disk prolapse group. In DDD and disk prolapses, subcutaneous fat was thicker in women ( p = 0.013 and 0.001). In patients with DDD, more subcutaneous fat was associated with disability ( p < 0.001). Muscle content of erector spinae and multifidus negatively correlated with increasing age in both groups at the L3–L4 level. Conclusions: Muscle fat content in the LPM does not appear to relate to PROMS. Muscle content decreases with age. Those with low back pain (DDD) have greater subcutaneous fat thickness.